Mozambique Diagnostic Review of Consumer Protection and Financial Literacy : Volume 2. Comparison with Good Practices - World Bank (World Bank, Washington, DC, 2017)
The review provides a detailed assessment of the institutional policy and regulatory framework in two segments of the financial sector: banking and non-bank credit institutions. The mission took place in response to a specific request for technical assistance in the field of financial consumer protection made by the central bank, the Banco de Moçambique (BdM), in November 2011. As agreed with the BdM, the assessment has focused on bank and non-bank entities within Mozambique’s financial sector that provide financial products and services to consumers, including microfinance, with a particular focus on credit reporting and on financial awareness. Volume one summarizes the key findings and recommendations of the review and volume two presents a detailed assessment of each financial segment compared to the good practices. Volume two also includes annexes that analyze and provide more detailed recommendations on credit reporting and financial education, and a description of the overall legal and institutional frameworks for financial consumer protection in Mozambique. The key findings and recommendations presented in this report cover six areas: institutional arrangements, legal and regulatory framework, disclosure, business practices, dispute resolution mechanisms, and financial education.